Diamine‐Functionalization of a Metal–Organic Framework Adsorbent for Superb Carbon Dioxide Adsorption and Desorption Properties. Issue 10 (30th April 2018) - Lee, Woo Ram; Kim, Jeong Eun; Lee, Sung Jin; Kang, Minjung; Kang, Dong Won; Lee, Hwa Young; Hiremath, Vishwanath; Seo, Jeong Gil; Jin, Hailian; Moon, Dohyun; Cho, Moses; Jung, Yousung; et al.
Abstract: For real‐world postcombustion applications in the mitigation of CO2 emissions using dry sorbents, adsorption and desorption behaviors should be controlled to design and fabricate prospective materials with optimal CO2 performances. Herein, we prepared diamine‐functionalized Mg2 (dobpdc) (H4 dobpdc=4, 4′‐dihydroxy‐(1, 1′‐biphenyl)‐3, 3′‐dicarboxylic acid). (1 ‐diamine) with ethylenediamine (en), primary–secondary ( N ‐ethylethylenediamine—een and N ‐isopropylethylenediamine—ipen), primary–tertiary, and secondary–secondary diamines. A slight alteration of the number of alkyl substituents on the diamines and their alkyl chain length dictates the desorption temperature ( T des ) at 100 % CO2, desorption characteristics, and Δ T systematically to result in the tuning of the working capacity. The existence of bulky substituents on the diamines improves the framework stability upon exposure to O2, SO2, and water vapor, relevant to real flue‐gas conditions. Bulky substituents are also responsible for an interesting two‐step behavior observed for the ipen case, as revealed by DFT calculations. Among the diamine‐appended metal–organic frameworks, 1 ‐een, which has the required adsorption and desorption properties, is a promising material for sorbent‐based CO2 capture processes. Hence, CO2 performance and framework durability can be tailored by the judicial selection of the diamine structure, which enables property design at will and facilitates the development of desirable CO2 ‐capture materials. Abstract : Catch it : A slight alteration of the number of alkyl substituents on the diamines and their alkyl chain length in diamine‐functionalized Mg2 (dobpdc) (H4 dobpdc=4, 4′‐dihydroxy‐(1, 1′‐biphenyl)‐3, 3′‐dicarboxylic acid) dictates the desorption temperature at 100 % CO2, desorption characteristics, and Δ T systematically, eventually resulting in the tuning of the working capacity. A correlation diagram between the working capacity and low‐pressure adsorption is established, which can be fine‐tuned by the type of diamine.